The origins, development, and application of Qualitative Comparative A nalysis: the first 25 years - Marx, Axel; Rihoux, Benoît; Ragin, Charles (European Political Science Review, 2014)
A quarter century ago, in 1987, Charles C. Ragin published The Compara tive Method, introducing a new method to the social sciences called Qu alitative Comparative Analysis (QCA). QCA is a comparative case-orient ed research approach and collection of techniques based on set theory and Boolean algebra, which aims to combine some of the strengths of qu alitative and quantitative research methods. Since its launch in 1987, QCA has been applied extensively in the social sciences. This review essay first sketches the origins of the ideas behind QCA. Next, the ma in features of the method, as presented in The Comparative Method, are introduced. A third part focuses on the early applications. A fourth part presents early criticisms and subsequent innovations. A fifth par t then focuses on an era of further expansion in political science and presents some of the main applications in the discipline. In doing so , this paper seeks to provide insights and references into the origin and development of QCA, a non-technical introduction to its main featu res, the path travelled so far, and the diversification of application s.